A new architecture for flexible shop control systems - Teunis, Gerrit (2010)
In the last two decades, there has been a marked trend in manufacturing away from function-centered production organisations towards product-based manufacturing shops and smaller organisational units. These new organisational structures reduce management complexity and facilitate greater human involvement and empowerment. Modern manufacturing facilities must be flexible, to allow for rapid reconfiguring of resources as dictated by variable demands. Today's tools for production planning and scheduling are not flexible enough, most of them being based on a certain production structure. A newly developed kernel/shell technology aims at a software architecture for shop control not being based on any assumption of the production structure. It should be possible to support almost any structure, organisation and scheduling algorithm. A central kernel acts as a service provider for a broad array of shell modules for scheduling, interfacing with legacy systems, database I/O, user interaction, SCADA interfacing, etc. This technology for shop control provides a high degree of customisation, flexibility and extendibility.